Cover-up or true? does CSR disclosure really contribute to corporate environmental performance? - Yun, Feifei; Lan, Tian; Chen, Yu (Frontiers in Environmental Science, 2023)
Do companies disclose their environmental social responsibility to demonstrate their good environmental performance or to cover up their poor environmental performance? This study examines the relationship between the disclosure level of corporate environmental responsibility information and corporate environmental performance based on institutional pressure, using data from Chinese A-share listed companies between 2008 and 2021. The results showed a negative relationship between the two variables, indicating that many firms might disclose environmental information to cover up their poor environmental performance. This phenomenon was more evident among non-state-owned enterprises and the enterprises in the economically underdeveloped regions. This study provides a new theoretical perspective for relevant management institutions to study social responsibility reports and formulate environmental protection policies.